200 years of national philologies: from romanticism to globalization - Strosetzki, Christoph (J.B. Metzler, 2023)
The 17 contributions in this volume pursue a positioning of the philologies, which - based on the 'Volksgeist' (popular spirit) of the 19th century and the cultural studies of the 20th century - must reposition themselves in the 21st century. The contributions address questions such as: What changes are occurring with increasing globalization? Are national literatures increasingly being absorbed into the so-called "world literature"? The authors come from the fields of Romance studies, German studies and English studies. They deal with topics of literary historiography, canonization, comparative literature, and also questions of the future. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
Keywords: Konferenzschrift -- 2019 -- Münster, Westfalen; Aufsatzsammlung; Geschichte 1820-2020; Literaturwissenschaft; Neuphilologie